SNAREpin Assembly by Munc18-1 Requires Previous Vesicle Docking by Synaptotagmin 1 - Parisotto, Daniel; Malsam, Jörg; Malsam, Andrea; Krause, Jean Michel; Söllner, Thomas (The journal of biological chemistry, 2012)
Regulated exocytosis requires the general membrane fusion machinery-soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) and Sec1/Munc18 (SM) proteins. Using reconstituted giant unilamellar vesicles containing preassembled t-SNARE proteins (syntaxin 1·SNAP-25), we determined how Munc18-1 controls the docking, priming, and fusion of small unilamellar vesicles containing the v-SNARE VAMP2 and the Ca2+ sensor synaptotagmin 1. In vitro assays allowed us to position Munc18-1 in the center of a sequential reaction cascade; vesicle docking by synaptotagmin 1 is a prerequisite for Munc18-1 to accelerate trans-SNARE complex (SNAREpin) assembly and membrane fusion. Complexin II stalls SNAREpin zippering at a late stage and, hence, contributes to synchronize membrane fusion in a Ca2+- and synaptotagmin 1-dependent manner. Thus, at the neuronal synapse, the priming factor Munc18-1 may accelerate the conversion of docked synaptic vesicles into a readily releasable pool by activating SNAREs for efficient membrane fusion.